#TITLE_ALTERNATIVE# - NATALIA BR GINTING (NIM : 12911042), DEVICA
This research examines the influence of local zonal wind, remote zonal wind forcing of Equatorial Indian Ocean (EIO) and Madden Jullian Osillation (MJO) towards the intraseasonal sea surface temperature (SST) variability at the coastal, transitional, and offshore areas of the Southeastern Tropical Indian Ocean (SETIO) using the SST, local zonal wind, remote zonal wind forcing in EIO (5°N - 5°S and 70°E - 90°E), the MJO index, and outgoing longwave radiation (OLR) for three years (2004 – 2006) data. The results of wavelet analysis show the SST at the coastal and transitional area dominantly influenced by the remote zonal wind forcing from the EIO while at the offshore area is influenced by local zonal winds. On the other hand, the method of Empirical Orthogonal Function (EOF) analysis is applied to observe the variances which influences the intraseasonal SST of the water. EOF results show three dominant modes (energy variant) with contribution 54% of the total variance, i.e. local zonal wind (32%), MJO (13%) and remote zonal wind forcing in EIO (9%).